367Association between dietary fatty acid intake, serum levels of fatty acids and ABCA1 DNA methylation. (2nd September 2021) - Fujii, Ryosuke; Yamada, Hiroya; Munetsuna, Eiji; Yamazaki, Mirai; Mizuno, Genki; Ando, Yoshitaka; Maeda, Keisuke; Tsuboi, Yoshiki; Ohashi, Koji; Ishikawa, Hiroaki; Hagiwara, Chiharu; Wakai, Kenji; et al.
Abstract: Background: Although previous studies have demonstrated that n-3 polyunsaturated fatty acids (PUFA) are inversely associated with a risk of CVD through gene expression, recent evidence suggests that it may arise from changes in DNA methylation. Therefore, we investigated whether dietary FA intake and serum FA levels are associated with ATP-binding cassette transporter A1 ( ABCA1 ), a gene associated with HDL-cholesterol metabolism. Methods: A total of 298 subjects (137 men, mean age of 63.2) without clinical history and medication participated in this cross-sectional study. We used the pyrosequencing method to measure DNA methylation levels at 8 CpG sites within ABCA1 gene and calculated mean DNA methylation level. Dietary FA intake were assessed with the food frequency questionnaire. Results: We found that ABCA1 DNA methylation levels were significantly lower with higher dietary intake of n-3PUFA (β = –5.75, p = 0.001), which is observed both in men (β = –4.85, p = 0.001) and women (β = –7.24, p = 0.007). In addition, ABCA1 DNA methylation levels were significantly lower with higher serum levels of n-3PUFA in men (β = –2.78, p = 0.05), but not in women (β = 1.61, p = 0.31). Conclusions: The results suggest that higher dietary n-3 PUFA intake and serum levels of n-3 PUFA are associated with lower ABCA1 DNA methylation in a Japanese population. Key messages: Higher dietary n-3 PUFA intake can be a prevention from dyslipidemia and CVD via low level of ABCA1 DNA methylation